Memahami Perbedaan Penghitungan Nisab Zakat Pedagang Busana Muslim Di Pasar Aur Kuning - Hary Elta Pratama; Eli Suryani Suryani; Mhd Yazid (Saqifah: Jurnal Hukum Ekonomi Syariah, 2023)
This research is motivated by the diversity of Muslim fashion traders in the Aur Kuning Konveksi Market, Bukittinggi City in calculating the trade zakat nishab. For further research, this research uses field research methods. Data collection techniques used interviews with 35 Muslim fashion traders and documentation. The collected data was processed and written using qualitative analysis which produced descriptive data. The findings in this research are that the calculation of the trade zakat nishab by Muslim fashion traders at the Aur Kuning Convection Market, Bukittinggi City has differences between one trader and another. This difference is influenced by several factors, including the level of understanding of traders regarding the nishab of trade zakat and the influence of existing culture, which makes traders only follow existing traditions without wanting to look for the correct source and in accordance with the provisions of trade zakat. It was also found that as many as 13% of the total 237 Muslim fashion traders did not calculate the nishab according to the provisions of trade zakat, such as calculating profits only, not calculating capital and debt, so the trade zakat paid was invalid.